2013
DOI: 10.1007/s13224-013-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Papp-A Level in the First Trimester of Pregnancy and Its Clinical Outcome

Abstract: Introduction Abnormalities in maternal serum marker levels and fetal measurements obtained during the first trimester screening can be a marker not only for certain chromosomal disorders and anomalies in the fetus but also for specific pregnancy complications. In particular, low maternal serum pregnancy-associated plasma protein-A (PAPP-A), at 11-13 weeks of gestation, is associated with stillbirth, infant death, intrauterine growth restriction, preterm birth, and pre-eclampsia in chromosomally normal fetuses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 12 publications
5
33
3
Order By: Relevance
“…Stillbirth was recorded in nine pregnancies in the low PAPP‐A cohort, compared with none in the control cohort. These findings are in line with the results of earlier studies . Conversely, normal PAPP‐A levels appeared to be an early marker of normal karyotype, normal fetal growth, and favorable pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Stillbirth was recorded in nine pregnancies in the low PAPP‐A cohort, compared with none in the control cohort. These findings are in line with the results of earlier studies . Conversely, normal PAPP‐A levels appeared to be an early marker of normal karyotype, normal fetal growth, and favorable pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…It is anticipated that, in this group of women, pregnancy outcomes would be less favorable compared with women with PAPP‐A levels closer to 1 MoM but would be considerably better compared with women with PAPP‐A levels below 0.3 MoM. It is expected that this would include most outcomes of interest, including aneuploidy, spontaneous abortion, preterm delivery, pre‐eclampsia, and SGA neonates …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dane et al [3] similarly reported PAPP-A to be a predictor of PT delivery in normotensive pregnancies. A significant inverse association between maternal serum PAAP-A and the risk of LBW but not with free beta hCG was reported by others [4][5][6].…”
Section: Discussionmentioning
confidence: 68%